ORGANIZATION ENGAGEMENT SEBAGAI MEDIATOR HUBUNGAN CALLING MEANING OF WORK DAN PSYCHOLOGICAL WELL-BEING (ENVIRONMENTAL MASTERY) (STUDI KASUS: PEKERJA PEREMPUAN): ORGANIZATION ENGAGEMENT AS A MEDIATOR ON RELATIONSHIP BETWEEN CALLING MEANING OF WORK AND PSYCHOLOGICAL WELL-BEING (ENVIRONMENTAL MASTERY) (CASE STUDY: WOMEN WORKER) - Silverius Y. Soeharso; Nanda Dwi Putri Utami (Jurnal Aplikasi Bisnis dan Manajemen (JABM), 2020)
This study aims to determine the effect of callings meaning of work on environmental mastery (one of the dimensions of psychological well-being) mediated by organizational engagement on the case of women workers in the garment industry at the Nusantara Industrial Bonded Zone (KBN). There were 111 participants, woman workers with a minimum of one year lenght of service. Data was collected through the environmental mastery adaptation scale instrument from Ryff (1989) (RPWBS) to measure Environmental Mastery, Amy Wrzesniewski's (1997) Work-Life Questionnaire and the scale of Organization Engagement from Saks (2006). Hypotheses are tested by Structural Equation Modeling (SEM), analyzed by Lisrel 8.7 software. The results showed that the model was declared fit, Organization engagement became the "full mediator" relationship between Callings (meaning of work) and Environmental Mastery (psychological well-being) wuth Chi-square 20.81; df = 24; p.value = 0.65003; RMSEA = 0,000. The managerial implication of this finding is that as long as the garment industry still relies on the role of women workers, management needs to improve a safe and comfortable work environment, and place leaders or supervisors who better understand and respect woman workers in their role in supporting organizational performance. Keywords: callings-meaning of work, organization engagement, environmental mastery indonesian, woman worker, garment industry